El labrinto de America Latina: ¿Hay otras salidas? - Quijano, Anibal (2005)
In recent years an intese debate has taken place on the current situation thatt latin America. Anibal Quijano proposes and devolops in this essay the thesis that we live a situation of increased economic crisis and of authentic catastrophe promoted by capitalist neoliberalism in all of Latin America. Then the author of this essay reviews the situation that involves the economy; the State, social actors and the world of the workers in a context of change u¿in the political geography. It concludes analizing the Brazilian exceptionality and the expansion process and invigoration of capitalism in Brazil in a colonial context imposed by the prevailing world power